Development of Questionnaire for Assistive Device Design in LPG Cylinder Handling - Al Amin, Mohamed Sultan; Isa , Halim; Nor Akramin, Mohamad; Febrian, Idral; Taufik (2014)
In Malaysia, Liquefied Petroleum Gas (LPG) is filled in a heavy steel cylinder and it is widely used for cooking purpose. Due to its dimensions and mass, the delivery men exposed to ergonomics risk factors associated with excessive force that can lead to injury to the back and the shoulders. There are assistive devices can be used to aid the delivery men; however, those devices are not efficient to transport the LPG cylinder to non-elevator apartments. Based on this reason, this study develops a questionnaire to determine design requirements of the assistive device for LPG cylinder handling. Structured interview using questionnaire survey was conducted among 25 delivery men. Based on the questionnaire survey, 76% of the delivery men required an assistive device that is safe, motorized, and push oriented for LPG cylinder handling. This study concluded that the developed questionnaire is reliable to determine design requirements of the assistive device for LPG cylinder handling.